2014
DOI: 10.1021/jp409798t
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium Ionic Response of Biased Mechanically Controllable Break Junction (MCBJ) Electrodes

Abstract: Novel experimental techniques allow for the manipulation and interrogation of biomolecules between metallic probes immersed in micro/nanofluidic channels. The behavior of ions in response to applied fields is a major issue in the use of these techniques in sensing applications. Here, we experimentally and theoretically elucidate the behavior of background currents in these systems. These large currents have a slowly decaying transient response, as well as noise that increases with ionic concentration. Using me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 55 publications
(87 reference statements)
1
29
0
Order By: Relevance
“…This point has already been discussed in a previous study. 22 As shown in Figure 10a, a measured electric signal was fitted by linear combinations of some exponents considering the time constants of τ e = 0.01, 0.1, 1, and 10 s. Using these constants, experimental data could be fitted by …”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This point has already been discussed in a previous study. 22 As shown in Figure 10a, a measured electric signal was fitted by linear combinations of some exponents considering the time constants of τ e = 0.01, 0.1, 1, and 10 s. Using these constants, experimental data could be fitted by …”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Numerical analysis of electric fields in the channel. Electrical potential distributions were numerically evaluated by solving the Nernst-Planck and Poisson equations 18,50 . The electrostatic potential is related to the electrical charge density as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Some numerical studies predicted an potential difference in electrolyte solutions as a function of ion concentration [14][15][16][17] . By solving the Nernst-Planck and Poisson equations, the relationship between the electrical potential and the concentration was clarified 18,19 . In particular, an electrode surface is strongly screened by electrolyte ions that form an electric double layer (EDL), and thus the applied electrical potential usually decreases near the surface.…”
Section: Development Of Glass Microelectrodes For Local Electric Fielmentioning
confidence: 99%
“…Recently, Doi et al reported on the transient electrical response of ions in the vicinity of biased electrodes. 106 Their results showed that ions rapidly responded to the strong fields near the electrode surface after turning on an applied voltage that screened the field in the process. Ions subsequently translocated in the weak electric field, and slowly relaxed within the diffusion layer.…”
Section: Environmental Influencesmentioning
confidence: 99%